On the hydracarina of Greenland with a description of Lebertia (Pseudolebertia) Groenlandica n. sp. - Letteval, Ulf (Meddelelser om Grønland, 1965)
In the summer of 1956 some water mites belonging to Lebertia (Pseudolebertia) groenlandica n. sp. were collected in three spring areas near Godhavn, Disko Island, Greenland. The description of the localities contains notes concerning their situation, exposure, bottom conditions and vegetation. A short survey on the physical and chemical conditions of the water is given from one of the spring areas (Østerli). Morphological comparisons are made between Lebertia groenlandica and three closely allied species, viz. Lebertia convergens, Lebertia glabra and Lebertia zschokkei. Finally, a list of Hydracarina finds from Greenland is given.